(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
In this article, information on family, family relations, conflicts that occur in modern families today, the social, economic, psychological factors that cause them, which are important objects of the social sphere, is presented. In Uzbekistan, information was given on the indicators of the increase in family Awards and disputes in recent years, the opinions of the head of our state, the role of social workers, veterans of the neighborhood, the general public and older people in the elimination and reduction of this social problem.